Is Digitalization Driving Domestic Inflation? - Csonto, Balazs (IMF Working Papers; Working Paper ;, 2019)
This paper examines the extent to which digitalization-measured by a new proxy based on IP addresses allocations per country-has influenced inflation dynamics in a sample of 36 advanced and emerging economies over 2000-2017. Phillips curve estimates show that digitalization has a statistically significant negative effect on inflation in the short run. Its economic impact is not large but has increased since 2012 and mainly operates through a cost/competition channel. Principal components and cointegration analysis further suggest digitalization is a key driver of lower trend inflation.